2021
DOI: 10.1111/fare.12571
|View full text |Cite
|
Sign up to set email alerts
|

Parenting During COVID‐19: A Study of Parents' Experiences Across Gender and Income Levels

Abstract: This study describes parenting experiences at the beginning of the COVID-19 pandemic and examines differences across parent gender and family income level. Background: The COVID-19 pandemic had unprecedented impacts on families. Many parents faced employment changes, including job loss, reduced pay, and working remotely, while simultaneously experiencing increased childcare responsibilities due to school and childcare closures. Research is needed to document the ongoing impact of these changes on parents and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(135 citation statements)
references
References 54 publications
12
88
0
5
Order By: Relevance
“…Initial pandemic research hypothesised that adverse changes to resilience and child-family wellbeing were likely [ 26 ]. More recent research suggested high anxiety and burnout amongst parents and increasing negative and positive expressed emotions [ 27 , 28 , 29 ], although, parenting flexibility appeared linked to greater family cohesion [ 30 ]. For women (and somewhat for parents), the pandemic has been described as exacerbating a triple work burden related to increasing productive, family, and community obligations [ 31 , 32 , 33 ], although not all findings support this [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial pandemic research hypothesised that adverse changes to resilience and child-family wellbeing were likely [ 26 ]. More recent research suggested high anxiety and burnout amongst parents and increasing negative and positive expressed emotions [ 27 , 28 , 29 ], although, parenting flexibility appeared linked to greater family cohesion [ 30 ]. For women (and somewhat for parents), the pandemic has been described as exacerbating a triple work burden related to increasing productive, family, and community obligations [ 31 , 32 , 33 ], although not all findings support this [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feedback from parents about concerns for children's health and economic problems, including availability of online learning support, are similar to reports from parents in the United States, who worried about the impact of closures on their children's daily routines, the spread of COVID-19, and demands of online schooling ( 21 ). Parents in the United States also reported high levels of depression, anxiety, parental burnout, and increased negative emotions, such as anger and worry ( 22 ). Our findings provide additional confirmation that school closures during COVID-19 are stressful for parents.…”
Section: Discussionmentioning
confidence: 99%
“…Karena dampak dari reaksi emosi ketika marah, jenuh atau bosan dan reaksi emosi lainnya akan membawa dampak yang mempengaruisikologi pada anak. Seperti hasil penelitian Margaret menemukan bahwa tingkat depresi yang tinggi, kecemasan, kelelahan, emosi negatif seperti mudah marah dan khawatir berlebihan disebabkan banyak orang tua yang menghadapi perubahan secara bersama mengalami peningkatan tanggung jawab dalam mengasuh anak selama dirumah Kerr (2021). Sehingga perlu mengetahui lebih lanjut lagi mengenai sikap dan emosi orang tua, Dan yang terpenting adalah bagaimana cara mengalihkan sikap dan emosi.…”
Section: " (Cuplikan Wawancara In)unclassified